2015
DOI: 10.3109/17483107.2015.1061613
|View full text |Cite
|
Sign up to set email alerts
|

Expanding stroke telerehabilitation services to rural veterans: a qualitative study on patient experiences using the robotic stroke therapy delivery and monitoring system program

Abstract: Telerehabilitation robotic devices can be used as a tool to extend effective, evidence-based and specialized rehabilitation services for upper and lower limb rehabilitation to rural Veterans with poor access to care. Implications for Rehabilitation Participants whose formal therapy services had ended either because they had exhausted their benefits or because traveling to outpatient therapy was too cumbersome due to distance were able to perform therapeutic activities in the home daily (or at least multiple ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(80 citation statements)
references
References 20 publications
2
77
0
1
Order By: Relevance
“…This reflects that even though people with stroke would agree to rely on assistive devices; still they want to feel independent while using such devices. Research conducted by Colleen O'Brien Cherry et al [38] resonated with our finding that users (people with stroke) reported that having a device that is easy to wear and to use is a crucial feature to accept a new assistive device. On contrast, both occupational and physical therapists did not mind to have complex devices to cover a larger spectrum of patients.…”
Section: Theme 1: "They Exist But…"supporting
confidence: 63%
“…This reflects that even though people with stroke would agree to rely on assistive devices; still they want to feel independent while using such devices. Research conducted by Colleen O'Brien Cherry et al [38] resonated with our finding that users (people with stroke) reported that having a device that is easy to wear and to use is a crucial feature to accept a new assistive device. On contrast, both occupational and physical therapists did not mind to have complex devices to cover a larger spectrum of patients.…”
Section: Theme 1: "They Exist But…"supporting
confidence: 63%
“…21 In contrast to tDCS, views and experiences of RT from people with stroke have been explored in three studies. 22,23,24 A small sample size of five participants with chronic stroke agreed that UL threedimensional RT was usable and that their arm felt stronger but not functionally improved. 23,24 Using observation and semi-structured interviews, ten participants with sub-acute and chronic stroke reported a home-based RT system was beneficial for their UL mobility, a positive outlet for releasing anxiety and increased their independence in activities of daily living and motivation.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 Using observation and semi-structured interviews, ten participants with sub-acute and chronic stroke reported a home-based RT system was beneficial for their UL mobility, a positive outlet for releasing anxiety and increased their independence in activities of daily living and motivation. 22 Barriers of use included technical difficulties and challenges when wearing and adjusting the device. The robot involved in this study promoted two-dimensional wrist movements but not functional shoulder, elbow and hand movements.…”
Section: Introductionmentioning
confidence: 99%
“…Low-cost gaming systems are increasingly being repurposed for applications in telerehabilitation, to deliver physical therapy to patients' homes and drive down the costs of treatment. Their affordability and portability can particularly benefit disadvantaged patient populations who cannot access quality medical care due to cost or geography [7][8][9] . By performing rehabilitative exercise at their convenience, patients can regain motor skills faster and accelerate their recovery toward reintegration into society.…”
Section: Discussionmentioning
confidence: 99%